Extracellular ATP triggers and maintains asthmatic airway inflammation by activating dendritic cells - Idzko, Marco; Hammad, Hamida; van Nimwegen, Menno; Kool, Mirjam; Willart, Monique A M; Muskens, Femke; Hoogsteden, Henk C; Luttmann, Werner; Ferrari, Davide; Di Virgilio, Francesco; Virchow, J Christian; Lambrecht, Bart N (Nature medicine, 2007)
Extracellular ATP serves as a danger signal to alert the immune system of tissue damage by acting on P2X or P2Y receptors. Here we show that allergen challenge causes acute accumulation of ATP in the airways of asthmatic subjects and mice with experimentally induced asthma. All the cardinal features of asthma, including eosinophilic airway inflammation, Th2 cytokine production and bronchial hyper-reactivity, were abrogated when lung ATP levels were locally neutralized using apyrase or when mice were treated with broad-spectrum P2-receptor antagonists. In addition to these effects of ATP in established inflammation, Th2 sensitization to inhaled antigen was enhanced by endogenous or exogenous ATP. The adjuvant effects of ATP were due to the recruitment and activation of lung myeloid dendritic cells that induced Th2 responses in the mediastinal nodes. Together these data show that purinergic signaling has a key role in allergen-driven lung inflammation that is likely to be amenable to therapeutic intervention.